2014
DOI: 10.1371/journal.pone.0094158
|View full text |Cite
|
Sign up to set email alerts
|

Whole Mitochondrial and Plastid Genome SNP Analysis of Nine Date Palm Cultivars Reveals Plastid Heteroplasmy and Close Phylogenetic Relationships among Cultivars

Abstract: Date palm is a very important crop in western Asia and northern Africa, and it is the oldest domesticated fruit tree with archaeological records dating back 5000 years. The huge economic value of this crop has generated considerable interest in breeding programs to enhance production of dates. One of the major limitations of these efforts is the uncertainty regarding the number of date palm cultivars, which are currently based on fruit shape, size, color, and taste. Whole mitochondrial and plastid genome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 44 publications
2
47
2
Order By: Relevance
“…Rather, this scattered occurrence can most easily be explained by the presence of heteroplasmic chloroplast genomes with homologous recombination between them. Thus, our study reveals for the first time incomplete lineage sorting in kelp species as it was shown in higher plants (Jakob & Blattner ; Sabir et al, ). The amount of SNPs per kb cannot be used to discern between coding and noncoding regions, since they are nearly equally distributed over the whole chloroplast genomes.…”
Section: Discussionsupporting
confidence: 68%
“…Rather, this scattered occurrence can most easily be explained by the presence of heteroplasmic chloroplast genomes with homologous recombination between them. Thus, our study reveals for the first time incomplete lineage sorting in kelp species as it was shown in higher plants (Jakob & Blattner ; Sabir et al, ). The amount of SNPs per kb cannot be used to discern between coding and noncoding regions, since they are nearly equally distributed over the whole chloroplast genomes.…”
Section: Discussionsupporting
confidence: 68%
“…; Sabir et al . ) and it has been shown that chloroplast heteroplasmy can evolve quickly to homoplasmy (Birky ; Greiner et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Sabir et al . ) on a single individual. Chloroplasts have a haploid genome, and consequently, SNPs are expected to be homozygous.…”
Section: Introductionmentioning
confidence: 99%
“…Duplication of those regions in the chloroplast genome and heteroplasmy cannot be ruled out. These processes have never been identified in the genus Pulsatilla, but they are increasingly often reported in other plant genera (Sabir et al, 2014;Szczecińska et al, 2014).…”
Section: Discussionmentioning
confidence: 99%